Treatment of Patients with COVID-19 and Concomitant Cardiovascular Diseases: Do not Forget About the Principles of Evidence-based Medicine - S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
The recent discussion about the dangers of using angiotensin-converting-enzyme (ACE) inhibitors and angiotensin II receptor antagonists (ARA) in patients with COVID-19 is analyzed in the article. There is controversy over the hypothesis that these drugs can be factors contributing to an unfavorable outcome of a viral disease, as well as the absence of any clinical evidence for this hypothesis. The opinion that withdrawal of ACE inhibitors and ARA in patients with COVID-19 may increase the risk of adverse outcomes is presented.